PENGEMBANGAN EVALUASI PEMBELAJARAN BERBASIS WORDWALL PADA ORGAN GERAK HEWAN DAN MANUSIA - Roshella Sylviana Sulaeman; Tatang Muhajang; Yudhie Suchyadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Rosella Sylviana Sulaeman. 037118059. Development of a wordwallbased learning evaluation on the theme of animal and human movement organs, sub-theme 3 of the environment and its benefits. Thesis. Pakuan University. Under the guidance of Tatang Muhajang, M. Ag. Dan Yudhie Suchyadi, M. Pd. Learning evaluation is a series of learning processes in order to determine the value or results of measuring learning outcomes. So that learning evaluation does not feel boring, it is necessary to develop a learning evaluation. This study aims to produce a wordwall-based learning evaluation product on the theme 1 animal and human movement organs, subtheme 3 environment and the benefits of 5th learning in class V SDN Police 1 Bogor City with a total of 28 students as respondents in the 2022/2023 academic year. This study uses the ADDIE model (analysis, design, development, implementation, evaluation). Field trials were carried out only on a limited basis. The instrument used in this study consisted of an expert validation sheet and a student response questionnaire instrument. The data analysis technique consists of a feasibility analysis of learning evaluation. The results showed that the wordwall-based learning evaluation that was developed was feasible to be used as an evaluation of learning in class V on theme 1 animal and human movement organs, sub-theme 3 environment and the benefits of 5th learning based on the average value of material expert validation of 94.4%, the average the average value of media validation is 86.7%, and the average value of language validation is 92%. Wordwall-based learning evaluation has effectiveness as a learning evaluation that does not bore the fifth grade students. This is evidenced from the posttest results in the form of a questionnaire given to students with a percentage of 95.71%.